Successful Aspiration Thrombectomy for Cocaine‐Induced Right Coronary Artery Embolism Secondary to Left Ventricular Thrombus: A Case Report and Literature Review - Abraam Rezkalla; Ahmad Nouri; Fadi Hadya; Islam Rajab; Emile Doss (Clinical Case Reports)
ABSTRACT Coronary embolism (CE) is a rare yet significant contributor to acute myocardial infarction (AMI), particularly in younger patients. We report a 42‐year‐old male who experienced an AMI following recent cocaine use. Investigations revealed a left ventricular apical thrombus, identified as the source of a distal embolus occluding the right coronary artery (RCA). Cocaine is known for its thrombogenic effects, promoting thrombus formation through mechanisms such as vasoconstriction and increased platelet aggregation. This unique situation highlights the critical interplay between cocaine use, left ventricular thrombus formation, and the resultant coronary artery embolism, contributing to myocardial ischemia. The patient underwent successful aspiration thrombectomy, restoring coronary blood flow without the need for stenting. This case underscores the importance of recognizing CE as a potential etiology of AMI, particularly in the context of substance abuse, advocating for heightened awareness among clinicians regarding the complexities of managing thromboembolic events.